2017
DOI: 10.1039/c7bm00207f
|View full text |Cite
|
Sign up to set email alerts
|

Successful PEGylation of hollow encapsulin nanoparticles from Rhodococcus erythropolis N771 without affecting their disassembly and reassembly properties

Abstract: We developed a hollow PEGylated encapsulin nanoparticle from Rhodococcus erythropolis N771. The hollow engineered encapsulin nanoparticles with His-Tag and Lys residues on the surface were constructed by means of genetic recombination. The Lys residues on the particle surface were successfully PEGylated with a PEG derivative, methoxy-PEG-SCM. Consequently, we demonstrated that the hollow PEGylated engineered encapsulin nanoparticle could successfully disassemble or reassemble even after PEGylation in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Moreover, the EH7‐K1 encapsulin nanoparticles were perfectly purified by gel filtration chromatography, because the nanoparticles are larger than contaminant proteins. These results are consistent with our previous report …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Moreover, the EH7‐K1 encapsulin nanoparticles were perfectly purified by gel filtration chromatography, because the nanoparticles are larger than contaminant proteins. These results are consistent with our previous report …”
Section: Resultssupporting
confidence: 94%
“…The difference demonstrates that the C ‐terminal Lys residue of the EH7‐K1 subunit functions as the target of PEGylation effectively. We confirmed that the encapsulin nanoparticles that derived from R. erythropolis N771 tended to aggregate as the amount of PEG bound to the Lys residues at C ‐termins increased . The EH7‐K1 encapsulin nanoparticles with high dispersibility are highly applicable in diverse research.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations